Costs of psychotropics for outpatients with bipolar disorder in Japan; the MUSUBI 2016 survey - Adachi, Naoto; Kubota, Yukihisa; Goto, Eiichiro; Watanabe, Koichiro; Yoshimura, Reiji; Tsuboi, Takashi; Yasui-Furukori, Norio; Kato, Masaki; Hongo, Seiji; Azekawa, Takaharu; Katsumoto, Eiichi; Edagawa, Koji; et al. (Annals of medicine (Helsinki), 2023)
Although the costs of bipolar disorder (BD) treatments are associated with local and universal factors, data from non-Western countries remain limited. The associations between clinical features and costs of outpatient pharmacotherapy have not been well characterize. To estimate the costs of outpatient BD treatments and their associations with clinical features in a Japanese population, we investigated with special reference to the costs of medicines constituted the bulk of the total healthcare expense and were steadily increasing. The Multicenter Treatment Survey for Bipolar Disorder (MUSUBI) retrospectively evaluated 3130 patients with BD who visited 176 Japanese psychiatric outpatient clinics in 2016. Clinical features and drug prescriptions were recorded, and the total daily costs of psychotropic drug treatment were calculated. The annual medical costs related to outpatient BD treatments in Japan were estimated based on the corresponding demographics. The associations between daily medical costs and patients' clinical features were analyzed using multiple regression analysis. The daily costs of psychotropic drugs ranged from zero to JPY3245 (mean, JPY349 equivalent to USD32.5) and were exponentially distributed. The annual costs for outpatients BD treatments were approximately 51.9 billion Japanese yens (519 million US dollars). Subsequent multiple regression analysis revealed that social adjustment, depressive symptoms, age, rapid cycling, psychotic symptoms, and comorbid mental disorders correlated strongly with the daily cost of psychotropic drugs. The estimated annual costs for outpatient BD treatment in Japan were equivalent to those in OECD countries (except for the US) and higher than those in some Asian countries. The cost of psychotropic treatments was associated with individual characteristics and psychopathological conditions. Key Messages Psychotropic treatment for an outpatient with bipolar disorder has a daily cost approximately JPY350. The annual outpatient treatment cost for bipolar disorder in Japan was estimated to 51.9 billion Japanese yen in 2016. Individual characteristics and psychopathological conditions affected the cost of drug treatment.